Journalistic Fraternity and the Ethical Representation of Islam in Nigeria - Alhaji Rabiu, Aliyu; Merican, Ahmad Murad (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
Abstract This paper investigates how the Nigerian journalistic fraternity shapes the ethical representation of Islam in news reporting, focusing on the impact of historical, institutional, and digital influences on journalists’ moral conduct. The problem addressed is the ethical misrepresentation of Islam, influenced by political, economic, and commercial pressures. A qualitative analytical approach is employed, combining textual analysis, a review of literature, professional codes, and Islamic moral injunctions to evaluate journalistic ethics in Nigeria’s pluralistic media environment. The study integrates interviews with 19 participants, including journalists, media experts, and Islamic scholars, using purposive sampling to ensure diverse perspectives. Participants were selected to represent a cross-section of the Nigerian media industry, encompassing various professional bodies, with a focus on their understanding and application of Islamic ethical principles such as ṣidq (truthfulness), ʿadl (justice), and amānah (trustworthiness). The findings reveal that political ownership, commercial pressures, and sensationalist practices have undermined journalistic ethics in Nigerian media. However, the study suggests that integrating Islamic communication ethics into journalism training and institutional practices could enhance media credibility, foster interreligious understanding, and promote social cohesion. The paper advocates for reforms in journalism education and professional practice, highlighting the potential for professional associations to lead ethical transformation. By proposing an Islamic moral framework, this research contributes to the discourse on media ethics and offers a path for re-envisioning ethical journalism in a multi-religious society like Nigeria.